DAMPAK PENERAPAN MODEL PROBLEM POSING BERBASIS MEDIA MACOBOX TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - Devi Murniawanti; Hesti Yunitiara Rizqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the differences in students' mathematical conceptual understanding before and after the implementation of the Problem Posing learning model assisted by MACOBOX (Mathematic Concept Box) and to examine its effect on elementary school students' conceptual understanding. This research employed a quantitative approach using a Pre-Experimental method with a One Group Pretest-Posttest Design. The participants consisted of 30 fourth-grade students of SDN Wirogomo 01 selected through saturated sampling. Data were collected using tests, questionnaires, observations, and documentation. The data were analyzed using the Shapiro-Wilk normality test, Paired Sample t-Test, and N-Gain analysis with IBM SPSS Statistics. The findings revealed a significant difference in students' mathematical conceptual understanding before and after the implementation of the Problem Posing learning model assisted by MACOBOX. The average pretest score increased from 66.67 to 86.00 in the posttest, while the average N-Gain score was 0.61, indicating a moderate level of improvement. The Paired Sample t-Test yielded a significance value (Sig. 2-tailed) of 0.000, which was lower than 0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. In addition, the conceptual understanding questionnaire obtained an average percentage score of 84.31%, categorized as very good. Therefore, it can be concluded that the Problem Posing learning model assisted by MACOBOX has a significant positive effect on fourth-grade students' mathematical conceptual understanding and can serve as an innovative, active, and meaningful instructional alternative for mathematics learning.